ACE Inhibitory and Antioxidant Activities of Collagen Hydrolysates from the Ribbon Jellyfi sh (Chrysaora sp.) - Barzideh, Zoha; Abd Latiff, Aishah; Gan, Chee Yuen; Abedin, Md. Zainul; Alias, Abd Karim (University of Zagreb, 2014)
Collagen isolated from the ribbon jellyfi sh (Chrysaora sp.) was hydrolysed using three diff erent proteases (i.e. trypsin, alcalase and Protamex) to obtain bioactive peptides. Angiotensin- I-converting enzyme (ACE) inhibitory activity and antioxidant activities (i.e. ferric reducing antioxidant power (FRAP) and 2,2-diphenyl-1-picrylhydrazyl (DPPH) radical scavenging activity) of the peptides were measured and compared, and the eff ect of the duration of hydrolysis on the bioactivity (ACE inhibitory and antioxidant activities) of peptides was also evaluated. FRAP activity was the highest in Protamex-induced (25–27 mM) and trypsin-induced hydrolysates (24–26 mM) at 7 and 9 h, respectively. Conversely, hydrolysates produced by trypsin for 1 and 3 h showed the highest DPPH radical scavenging activities (94 and 92 %, respectively). Trypsin-induced hydrolysates (at 3 h) also showed the highest ACE inhibitory activity (89 %). The peptide sequences with the highest activities were identifi ed using tandem mass spectrometry, and the results show that the hydrolysates had a high content of hydrophobic amino acids as well as unique amino acid sequences, which likely contribute to their biological activities.